Isotemporal substitution of sleep or sedentary behavior with physical activity in the context of frailty among older adults: a cross-sectional study - Martins, Giovana Silva; Galvão, Lucas Lima; Tribess, Sheilla; Meneguci, Joilson; Virtuoso Júnior, Jair Sindra (São Paulo Medical Journal, 2023)
BACKGROUND: Frailty syndrome is associated with various physical, cognitive, social, economic, and environmental factors. Although frailty syndrome occurs progressively with age, prevention and treatment are possible. Reducing or eliminating risks and increasing protective factors may be potential strategies for reducing the prevalence of injuries related to frailty. One of the most effective actions is to decrease the time spent in sedentary behavior (SB) by increasing regular physical activity (PA). OBJECTIVE: To examine the hypothetical effect of substitution of the time spent in sleep or SB with an equivalent time spent performing moderate or vigorous PA on frailty syndrome in the older population. DESIGN AND SETTING: An analytical cross-sectional study conducted using exploratory methods of survey, carried out in Alcobaça city, Bahia, Brazil. METHODS: A total of 456 older adults of both sexes, aged ≥ 60 years, participated in this study. Frailty syndrome was identified according to the criteria of the Study of Osteoporotic Fractures. PA and SB were assessed using the International Physical Activity Questionnaire, and sleep was assessed using the Pittsburgh Sleep Quality Index. The effects of time substitution on these behaviors were verified using Poisson regression. RESULTS: The replacement of 60 min/day of SB (prevalence ratio, PR = 0.52; 95% confidence interval, CI: 0.28–0.96) or sleep (PR = 0.52; 95% CI: 0.27–0.98) with 60 min/day of moderate PA (MPA) was associated with a 48% reduction in the prevalence of frailty syndrome. CONCLUSIONS: Replacing the time spent sitting or sleeping with the same amount of MPA time may reduce frailty; the longer the duration of time spent in the substitution of sleep or SB with MPA, the greater the benefits.